Practical Strategies for Stimulating Creativity in Early Childhood: STEAM Approach, Parent Involvement, and Environmental Support - Anjani, Ratna (Seulanga : Jurnal Pendidikan Anak, 2024)
This research aims to explore practical strategies that educators and parents can implement in stimulating early childhood creativity in Indonesia. Creativity plays an important role in children's cognitive, social and emotional development and is an essential skill in facing the challenges of the 21st century. Despite its importance, the development of creativity in early childhood in Indonesia still faces various barriers, including teachers' lack of understanding of creative teaching methods and parents' involvement in supporting an environment conducive to children's creativity. This research uses the literature review method by analyzing various relevant sources from national and international journals. The results show that the application of creative methods such as the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach, educational games, and art activities can effectively stimulate children's creativity. In addition, active involvement of parents and environmental support that supports exploration also play a significant role in the development of creativity. This research is expected to make theoretical and practical contributions in improving the quality of early childhood education in Indonesia through the implementation of more innovative creativity development strategies.